Digital technology adoption, digital dynamic capability, and digital transformation performance of textile industry: Moderating role of digital innovation orientation. (3rd December 2021) - Shen, Lei; Zhang, Xi; Liu, Hongda
Abstract : In the new manufacturing area, the Chinese textile industry is facing the opportunities and challenges under the sustainable development model and advanced manufacturing technology. It is urgent to use digital technology to realize digital transformation. In this process, digital dynamic capability and digital innovation are significant for textile firms to achieve digital transformation performance. Drawing on the data from 367 questionnaires of Chinese textile firms, we apply multiple regression to examine how a firm's digital transformation is affected by adopting digital technology. A conceptual model based on framework of resource–capability–performance is developed to examine how adoption of digital technology, digital dynamic capability, and digital innovation orientation affects a firm's digital transformation performance. The results indicate that the positive relationship between digital technology adoption and digital transformation performance is less significant; this path is fully mediated through digital dynamic capability. Digital innovation orientation has a positive moderating effect and that the efficiency digital innovation has the most significant moderating effect among all digital innovation types. In addition, compared with textile firms in the low level of digital technology adoption, the firms in the high‐level group show a significant positive relationship between digital technology adoption and digital transformation performance. These findings confirm the validity of the model and contribute to existing literature on technology efforts in firms and provide guidelines to help managers implement informed decisions about digital transformation.